Analisa Efektifitas Persediaan Usaha Mikro Kecil Dan Menengah (UMKM) Dinara Bolen’s Menggunakan Metode Economic Order Quantity (EOQ) - Lestari, Alfiani Ayu; Apriyanti, Apriyanti; Islami, Rizqa Aulia; Aryani, Windy (Journal of Economics and Management, 2024)
UMKM Dinara Bolen's Karawang is one of the culinary that has succeeded in providing a touch of distinctive taste of Karawang Regency. The development of this business has an impact on the number of materials that must be ready to be used for production. Failure to manage inventory can have an impact on production delays which can disappoint buyers because product stocks are empty. This research was conducted to analyze whether the inventory system used by the company has reached the maximum and effective number, which can then be used as a consideration for Dinara Bolen's Karawang MSMEs to be applied as a basis for procuring inventory. This type of research is descriptive qualitative.The data to be collected by researchers is based on information obtained when meeting directly with informants. Primary data were obtained from observations and interviews with research subjects. This research also has the result that using the Economic Order Quantity (EOQ) method can produce a reference for accommodating inventory by only spending 35% of the total usual expenditure, which also helps in calculating stored inventory to be called Safety Stock. From the inventory cost analysis, Dinara Bolen's Karawang MSMEs can apply the time and amount of purchasing production materials.